Influence of OCT1 Ontogeny and Genetic Variation on Morphine Disposition in Critically Ill Neonates: Lessons From PBPK Modeling and Clinical Study. Issue 3 (8th November 2018) - Hahn, David; Emoto, Chie; Euteneuer, Joshua C.; Mizuno, Tomoyuki; Vinks, Alexander A.; Fukuda, Tsuyoshi
Abstract : Morphine is commonly used for analgesia in the neonatal intensive care unit (NICU) despite having highly variable pharmacokinetics (PKs) between individual patients. The pharmacogenetic (PG) effect of variants at the loci of organic cation transporter 1 ( OCT1 ) and UDP‐glucuronosyltransferase 2B7 ( UGT2B7 ) on age‐dependent morphine clearance were evaluated in a cohort of critically ill neonatal patients using an opportunistic sampling design. Our primary results demonstrate the significant influence of OCT1 genotype ( P < 0.05) and gestational age ( P ≤ 0.005) on morphine PKs. A physiologically based pharmacokinetic (PBPK) model for morphine that accounted for OCT1 ontogeny and PG effect in post‐term neonates adequately described the clinically observed variability in morphine PKs. This study serves as a proof of concept for genotype‐dependent drug transporter ontogeny in neonates.